2013
DOI: 10.1038/oncsis.2013.28
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitination of Dishevelled by Usp14 is required for Wnt signaling

Abstract: Dishevelled (Dvl) is a key regulator of Wnt signaling both in the canonical and non-canonical pathways. Here we report the identification of a regulatory domain of ubiquitination (RDU) in the C-terminus of Dvl. Mutations in the RDU resulted in accumulation of polyubiquitinated forms of Dvl, which were mainly K63 linked. Small interfering RNA-based screening identified Usp14 as a mediator of Dvl deubiquitination. Genetic and chemical suppression of Usp14 activity caused an increase in Dvl polyubiquitination and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 34 publications
4
85
0
Order By: Relevance
“…We have previously shown that USP14 levels strongly correlate with β-catenin-mediated colon cancer development [35]. Among colon cancer cell lines, SW480, LOVO, DLD1, and Caco2 colon cancer cells have significantly or modestly increased levels of USP14 in contrast to HEK293 cells or HCT116 cells, which have lost USP14 expression because of somatic mutations [35].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that USP14 levels strongly correlate with β-catenin-mediated colon cancer development [35]. Among colon cancer cell lines, SW480, LOVO, DLD1, and Caco2 colon cancer cells have significantly or modestly increased levels of USP14 in contrast to HEK293 cells or HCT116 cells, which have lost USP14 expression because of somatic mutations [35].…”
Section: Resultsmentioning
confidence: 99%
“…␤-Catenin, the key effector of the pathway, has been found to be targeted by multiple E3 ligases that are regulated by distinct stimuli in different contexts (12)(13)(14)(15)(16)(17). The roles of deubiquitinating enzymes in controlling the Wnt/␤-catenin pathway have also been exemplified in several studies, wherein they target either ␤-catenin, APC, or axin (20,21,37). Our present study extends these findings by defining for the first time the RING finger ubiquitin E3 ligase RNF220 as a ␤-catenin stabilizer through USP7-mediated deubiquitination, thereby suggesting a previously unknown broader role of ubiquitin E3 ligases.…”
Section: Discussionmentioning
confidence: 99%
“…Although the deubiquitinase FAM (USP9X) is able to target and stabilize ␤-catenin, it has been suggested to be mainly involved in the trafficking of ␤-catenin and E-cadherin in epithelia (19). USP14 was also found to be overexpressed in lung adenocarcinoma and able to stabilize ␤-catenin; however, it was shown to work by directly targeting the upstream regulator Dishevelled (Dvl) (20,21).…”
mentioning
confidence: 99%
“…S4), we hypothesized that USP14 might regulate autophagy through a nondegradative mechanism independently of K48 ubiquitination. Since USP14 can deubiquitinate K63 ubiquitin linkage (Jung et al 2013;Xu et al 2015a;Lee et al 2016), we considered the possibility that USP14 may regulate autophagy by deubiquitinating K63 ubiquitinated proteins. To directly test this possibility, we performed a quantitative mass spectrometry analysis to compare the changes in K63 ubiquitinated proteins with H4 cells expressing USP14 wild type and those expressing vector only or the USP14-AA mutant (Fig.…”
Section: Usp14 Regulates Beclin 1 K63-linked Ubiquitinationmentioning
confidence: 99%